Investigation of Enhanced Transmission and Beaming Effect Through an InSb Subwavelength Grating With a Slit at the Terahertz Range - Xinyi Liu; Yan Liu; Cizhe Fang; Genquan Han; Yue Hao (IEEE Photonics Journal)
In this paper, we demonstrate the feasibility of realizing the extraordinary optical transmission (EOT) and the collimated beaming effect through InSb grating, which has a subwavelength slit surrounded by a finite array of grooves at both sides of the surface. Firstly, we investigate the transmission properties of the structure by changing the temperature and doping concentration of InSb, and the optimized transmission can reach almost 95%. Besides, it is verified that the transmission is mainly controlled by the pattern on the input corrugation with the variable dimension parameters. At last, the properties of the beaming intensity and focal length are thoroughly analyzed with the variation of the number and depth of the grooves on the output corrugation. These results provide a new plasmonic solution for controlling light in a variety of integrated optical components in the terahertz range.